1990
DOI: 10.1002/j.1460-2075.1990.tb08073.x
|View full text |Cite
|
Sign up to set email alerts
|

The early nodulin transcript ENOD2 is located in the nodule parenchyma (inner cortex) of pea and soybean root nodules.

Abstract: A pea cDNA clone homologous to the soybean early nodulin clone pGmENOD2 that most probably encodes a cell wall protein was isolated. The derived amino acid sequence of the pea ENOD2 protein shows that it contains the same repeating pentapeptides, ProProHisGluLys and ProProGluTyrGln, as the soybean ENOD2 protein. By in situ hybridization the expression of the ENOD2 gene was shown to occur only in the inner cortex of the indeterminate pea nodule. The transcription of the pea ENOD2 gene starts when the inner cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
5

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(119 citation statements)
references
References 18 publications
4
110
0
5
Order By: Relevance
“…The senescent zone (zone IV) is not seen in these examples but is apparent in 12-day-old /n,Sar nodules (Figures 7G and 7H). The nodule parenchyma (inner cortex; Van de Wiel et al, 1990), nodule vascular bundles, and the (A) Total RNA (10 ^.g), isolated from roots (R; day 5 or 6) and nodules (days 9 and 12) of Saranac plants inoculated with either effective R. meliloti 102F51 or ineffective strains T202, G456, 1491, or F642, as indicated, was electrophoresed in a 1.5% formaldehydeagarose gel, transferred to a ZetaProbe membrane, and probed with 32 P-labeled AS13. (B) Radioactivity in the 2.2-kb AS band on each sampling date was determined by AMBIS radioanalytic image analysis.…”
Section: Localization Of As Transcripts In Effective and Ineffective mentioning
confidence: 99%
See 1 more Smart Citation
“…The senescent zone (zone IV) is not seen in these examples but is apparent in 12-day-old /n,Sar nodules (Figures 7G and 7H). The nodule parenchyma (inner cortex; Van de Wiel et al, 1990), nodule vascular bundles, and the (A) Total RNA (10 ^.g), isolated from roots (R; day 5 or 6) and nodules (days 9 and 12) of Saranac plants inoculated with either effective R. meliloti 102F51 or ineffective strains T202, G456, 1491, or F642, as indicated, was electrophoresed in a 1.5% formaldehydeagarose gel, transferred to a ZetaProbe membrane, and probed with 32 P-labeled AS13. (B) Radioactivity in the 2.2-kb AS band on each sampling date was determined by AMBIS radioanalytic image analysis.…”
Section: Localization Of As Transcripts In Effective and Ineffective mentioning
confidence: 99%
“…In situ hybridization was performed essentially as described by Van de Wiel et al (1990). At least 20 day 12 Saranac and in,Sar nodules were fixed with 4% paraformaldehyde and 0.25% glutaraldehyde in 50 mM sodium phosphate buffer, pH 7.2, at room temperature.…”
Section: Plant Dna Extraction and Dna Gel Analysismentioning
confidence: 99%
“…The first 24 deduced amino acids were found to display typical characteristics of signal peptides Werner and Schatz, 1988) and share a high degree of homology with the putative signal sequences of the soybean €nod2 (Franssen et a/., 1989) and Enodl2 (Scheres etal., 1990) gene products (data not shown). The remainder of the deduced protein sequence consists of a 55-fold repeat of short proline-rich oligopeptides ( Figure 2), thereby resembling EnodZproteins from other legumes (Dickstein eta/., 1988;Franssen eta/., 1987Franssen eta/., ,1989Govers etal., 1990;Szczyglowski and Legocki, 1990;Van de Wiel et a/., 199Oa). With a few exceptions, these proline-rich peptide repeats can be subdivided into two classes, represented by the following amino acid motifs: (X-)X-GIuLys-Pro-Pro-(Pro), repeated 30-fold, and X-Tyr-(X-)ProPro-(Pro), repeated 19-fold (Figure 2).…”
Section: /Solation and Characterization Of The Srenod2 Locusmentioning
confidence: 99%
“…PRPs were first identified as proteins that accumulate in the cell wall in response to physical damage (Chen and Varner, 1985;Tierney et al, 1988) and have subsequently been shown to be temporally regulated during plant development. PRP gene expression is associated with early stages of legume root nodule formation (Franssen et al, 1987;van de Wiel et al, 1990;Wilson et al, 1994), soybean seedling, leaf, stem, and seed coat development (Hong et al, 1989;Kleis-San Francisco and Tierney, 1990;Lindstrom and Vodkin, 1991;Ye et al, 1991), bean seedling growth (Sheng et al, 1991), and with early stages of tomato fruit development (Santino et al, 1997). The spatial pattern of PRP expression is also tightly regulated, as shown by in situ hybridization and reporter gene expression analysis (Wyatt et al, 1992;Suzuki et al, 1993).…”
mentioning
confidence: 99%